Environmental factors of commuting accidents among firefighter drivers in Peninsular Malaysia: a case study - Norfaqihah Mohtar,; Rosnah Ismail,; Nor Hisham Mohammad,; Mohammad Paisal Adam,; Mohammad Hamdan Wahid,; Mohd Hasni Ja’afar, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Commuting accidents (CAs) caused significant detrimental impacts on the Fire and Rescue Department of Malaysia (FRDM). Therefore, this study aims to identify factors of CA by mainly focusing on environmental factors. The qualitative data was obtained from FRDM accident investigation reports from five states (Kedah, Selangor, Kuala Lumpur, Negeri Sembilan and Johor) between 2017-2021. The data were analysed using content analysis. Four environmental factors that contribute to CA were identified. The factors were environmental conditions (rainfall, strong wind, light glare, and insufficient lighting), time (twilight and night time), road physical conditions (hilly road, curvy, steep, and narrow road, weak manhole cover, soft ground, wet and slippery road), and road environment (traffic congestion and sudden animal crossing). These findings provide environment-related hazards input for risk assessment and management of CA in FRDM, as well as valuable information for future research. Therefore, it has the potential to improve road safety for firefighters, the general public, and animals.